Transformation of the System of Training Specialists during the Transition to FSES 3++ - R. N. Bakhtizin; O. A. Baulin; R. M. Mazitov; N. A. Shaikhutdinova (Высшее образование в России)
Currently, the universities in the Russian Federation are engaged in the updating of the educational programs being implemented, in accordance with the requirements of the Federal State Educational Standard 3 ++. The article provides information on the conceptual changes in the State Educational Standard, Federal State Educational Standard, and Federal State Educational Standard 3 ++ , as well as on the new opportunities universities have in connection with the introduction of the “two plus” generation standard. By an example of the project “NetworkElectronicUniversityof theRepublicofBashkortostan” the article shows the network interaction on issues of the formation of universal competences. New opportunities for universities during the transition to FSES 3 ++ are considered in the context of globalization conditions. The universities are suggested to be considered not so much as a “talent foundry”, but rather as a presence territory development driver, a space for constant positive changes (4P) due to the comprehensive development of scientific, innovative, socio-cultural activities with concurrent integration into the educational environment. The implementation of such a model within the transition to FSES 3 ++ is proposed to be done by individualizing mass education, building flexible educational trajectories that most meet the needs of the parties involved. At the same time, the so-called soft skills should become an indispensable superstructure for the formation of professional competencies, as without them it is extremely difficult to train specialists able to adapt as quickly as possible to changes in the external environment, and, in conditions of uncertainty of occupational functions in the future, they become more important than hard skills.